Role of the HLA-DQ locus in the development of chronic gastritis and gastric carcinoma in Mexican patients - Roberto Herrera-Goepfert Jesús K Yamamoto-Furusho Luis F Onate-Ocana Margarita Camorlinga-Ponce Leopoldo Munoz Jorge A Ruiz-Morales Gilberto Vargas-Alarcón Julio Granados (World journal of gastroenterology : WJG, 2006)
AIM： To determine the HLA-DQ locus in Mexican patients with Chronic gastritis and gastric adenocarcinoma. METHODS： Oligotyping for HLA-DQ locus was performed in 45 Mexican patients with chronic gastritis and 13 Mexican patients with diffuse-type gastric adenocarcinoma, and was then compared with 99 clinically healthy unrelated individuals. H pylori infection and CagA status were assessed in patients by enzyme-linked immunosorbent assay （EUSA） method. RESULTS： We found a significant increased frequency of HLA-DQBI＊0401 allele in Hpylori-positive patients with chronic gastritis when compared with healthy subjects [19 vs 0%, P = 1 × 10^-7, odds ratio （OR） = 4.96; 95% confidence interval （95% CI）, 3.87-6.35]. We also found a significant increased frequency of HLA-DQBI＊0501 in patients with diffuse-type gastric carcinoma in comparison with healthy individuals （P = 1 × 10^4, OR = 13.07; 95% CI, 2.82-85.14）. CONCLUSION： HLA-DQ locus may play a different role in the development of H pylori-related chronic gastritis and difffuse-type gastric adenocarcinoma in the Mexican Mestizo population.